2015
DOI: 10.1002/cam4.497
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of capecitabine, oxaliplatin, and irinotecan in combination with bevacizumab in first line treatment of metastatic colorectal cancer

Abstract: Phase III studies have demonstrated the efficacy of FOLFOXIRI regimens (5-fluorouracil/leucovorin, oxaliplatin, irinotecan) with/without bevacizumab in metastatic colorectal cancer (mCRC). Capecitabine is an orally administered fluoropyrimidine that may be used instead of 5-fluorouracil/leucovorin. We evaluated a triple-chemotherapy regimen of capecitabine, oxaliplatin, and irinotecan, plus bevacizumab in 53 patients with mCRC. A Phase I study identified the maximum tolerated dose of irinotecan as 150 mg/m2. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…A phase 1/2 study including 54 patients evaluated the combination of CAPOXIRI plus bevacizumab. [49] Efficacy in terms of response rates (64.4%), median PFS (16 months), and median OS (28 months) was comparable to the efficacy observed in the trials evaluating FOLFOXIRI regimens. [47,48] However, toxicity levels were high, with higher incidences of grade 3 or 4 diarrhea (36%), neutropenia (32%), and nausea/vomiting (21%).…”
Section: Capoxiri Plus Bevacizumabsupporting
confidence: 53%
“…A phase 1/2 study including 54 patients evaluated the combination of CAPOXIRI plus bevacizumab. [49] Efficacy in terms of response rates (64.4%), median PFS (16 months), and median OS (28 months) was comparable to the efficacy observed in the trials evaluating FOLFOXIRI regimens. [47,48] However, toxicity levels were high, with higher incidences of grade 3 or 4 diarrhea (36%), neutropenia (32%), and nausea/vomiting (21%).…”
Section: Capoxiri Plus Bevacizumabsupporting
confidence: 53%
“…The medical records of patients treated with triplet chemotherapy consisting of irinotecan, oxaliplatin, and capecitabine (Bazarbashi et al, 2015) in combination with bevacizumab on a prospective clinical trial (clinicaltrial. gov: NCT01311050), were retrospectively reviewed for the location of the primary tumor.…”
Section: Methodsmentioning
confidence: 99%
“…There is also smaller evidence from post-hoc analysis which showed that patient with right-sided metastatic disease benefit more from upfront triplet chemotherapy regimens than patients with left-sided tumors (Cremolini et al, 2015). We have previously published our results with the combination of capecitabine, oxaliplatin, irinotecan, and bevacizumab in the first-line setting of metastatic colorectal cancer within a phase I-II trial (Bazarbashi et al, 2015). In this analysis, we report the outcome of patients with right-sided versus left-sided primary tumors in patients treated on the above study and examine if triplet therapy does overcome the poor prognosis of right-sided metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The realization has been increasing that the triple combination will benefit patients with gastrointestinal tumors. Further evaluations have been conducted in patients with mCRC in combinations with bevacizumab, 29,30 neoadjuvant rectal cancer (unpublished data), or metastatic gastric cancer. 31,32 Conclusion IXO administered every 3 weeks as first-line therapy for mCRC is highly active by improving the response rate and survival.…”
Section: Jean Maroun Et Almentioning
confidence: 99%